2018
DOI: 10.1016/j.bjm.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of decolorization of different dyes using fungal biomass immobilized on different solid supports

Abstract: Different technologies may be used for decolorization of wastewater containing dyes. Among them, biological processes are the most promising because they seem to be environmentally safe. The aim of this study was to determine the efficiency of decolorization of two dyes belonging to different classes (azo and triphenylmethane dyes) by immobilized biomass of strains of fungi (Pleurotus ostreatus – BWPH, Gleophyllum odoratum – DCa and Polyporus picipes – RWP17). Different solid supports were tested for biomass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 63 publications
4
32
0
4
Order By: Relevance
“…5). In generally, the higher DE by live cells as opposed to dead cells has been reported in other studies as well Ting et al (2016); Przystas et al (2018); . This has been primarily attributed to the biodegradation of live cells because they can produce the lignin modifying enzymes, such as MnP, LiP and Lac (Srinivasan and Viraraghavan 2010; Marcharchand and Ting 2017; Munck et al 2018).…”
Section: Biomass Absorption or Adsorption And Enzymolysis Contributiosupporting
confidence: 81%
See 1 more Smart Citation
“…5). In generally, the higher DE by live cells as opposed to dead cells has been reported in other studies as well Ting et al (2016); Przystas et al (2018); . This has been primarily attributed to the biodegradation of live cells because they can produce the lignin modifying enzymes, such as MnP, LiP and Lac (Srinivasan and Viraraghavan 2010; Marcharchand and Ting 2017; Munck et al 2018).…”
Section: Biomass Absorption or Adsorption And Enzymolysis Contributiosupporting
confidence: 81%
“…Currently, with the wide application of synthetic dyes, their e uents could cause severe damage to the environment. As one of the most important groups of synthetic dyes, triphenylmethane (TPM) dyes such as cotton blue (CB), crystal violet (CV), malachite green (MG) and methyl violet (MV) in textile, leather, cosmetic, pharmaceutical and paper industries poses a direct threat to the environment due to the toxic and carcinogenicity of their degradation products (Daneshvar et al, 2007;Chaudhry et al 2014; Barapatre et al 2017;Przystas et al 2018). As a consequence, effective removal of hazardous TPM dyes from the aqueous solutions as well as detoxi cation is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports use technology to improve textile processes and reduce environmental pollutants [7,8]. It is predictable that, the liberalization of 10 -15% of dyes in the treated water [9], which affect the photosynthetic activities in aquatic life by reducing the intensity of light propagation that may also be lethal to some aquatic animals and plants due to the attendance of aromatic materials, metals, chlorides and because of high biochemical oxygen demand (BOD), COD and low biodegradability [10,11]. Inspite of the dyes, textile effluent additionally contains variable pH and ionic strength, and high concentration of salts.…”
Section: Introductionmentioning
confidence: 99%
“…have the capacity to produce a significant amount of mycelial mass because of their efficiency, and being one of the most cultivated fungi, they have extensive applicability in biological processes. The fungi are able to grow in different media due to their ability to secrete enzymes to absorb the nutrients necessary for their development (Przystaś et al, 2018). The analysis of the production of fungal mycelial mass (Figure 1) showed that, except for isolate P3, almost all the isolates in the solution with the PD medium were able to produce a higher mycelial mass compared to the other solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the superficial contacts with the contaminants are optimized, thereby increasing their bioavailability and consequently, their biodegradation (Przystaś et al, 2018).…”
Section: Introductionmentioning
confidence: 99%